2019
DOI: 10.1523/eneuro.0300-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Interneuron Development in a Novel Model of Neonatal Brain Injury

Abstract: Prematurity is associated with significantly increased risk of neurobehavioral pathologies, including autism and schizophrenia. A common feature of these psychiatric disorders is prefrontal cortex (PFC) inhibitory circuit disruption due to GABAergic interneuron alteration. Cortical interneurons are generated and migrate throughout late gestation and early infancy, making them highly susceptible to perinatal insults such as preterm birth. Term and preterm PFC pathology specimens were assessed using immunohistoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
35
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 71 publications
(78 reference statements)
10
35
2
Order By: Relevance
“…In the present study, cerebral ischemia in near-term fetal sheep was associated with a pattern of parasagittal cortical damage after 7 days of recovery, which included a marked reduction in the survival of cortical GAD + , parvalbumin + , calretinin + , and calbindin + interneuron populations. These findings are broadly consistent with previous studies showing loss and disrupted development of interneurons in the cerebral cortex and subcortical grey matter following HI in preterm and term fetal sheep [17,[32][33][34][35] and neonatal rodents [36][37][38][39][40][41][42][43] and following ventilatory support in preterm baboons [44]. Although there are no comparable term human data, limited pathology and imaging studies in preterm infants have shown reductions in the numbers and complexity of cortical interneurons, refs [25,45] cortical interneuron migration, [7] interneuron neurogenesis, [46] and cortical GABAergic signaling [4].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, cerebral ischemia in near-term fetal sheep was associated with a pattern of parasagittal cortical damage after 7 days of recovery, which included a marked reduction in the survival of cortical GAD + , parvalbumin + , calretinin + , and calbindin + interneuron populations. These findings are broadly consistent with previous studies showing loss and disrupted development of interneurons in the cerebral cortex and subcortical grey matter following HI in preterm and term fetal sheep [17,[32][33][34][35] and neonatal rodents [36][37][38][39][40][41][42][43] and following ventilatory support in preterm baboons [44]. Although there are no comparable term human data, limited pathology and imaging studies in preterm infants have shown reductions in the numbers and complexity of cortical interneurons, refs [25,45] cortical interneuron migration, [7] interneuron neurogenesis, [46] and cortical GABAergic signaling [4].…”
Section: Discussionsupporting
confidence: 92%
“…To support the stringency of our findings, future studies would be beneficial to further characterize the dying neurons within the subplate zone of the posterior parietal cortex to confirm their subplate neuronal identity and to differentiate them from forkhead box protein 1 (foxp1)-expressing neighboring neurons from cortical layers II–V [18]. Additionally, a very recent study showed that the loss of GABA-ergic interneurons within the prefrontal cortex in a novel mouse model of preterm brain injury lead to specific working memory deficits and neurobehavioral deficits which parallel human psychopathologies seen in preterm birth survivors [58]. Further investigations would be required to analyze whether there are also GABA-ergic interneurons among the dying cells within the parietal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Postmortem studies have indicated a significant loss of GABAergic interneurons in premature infants 36,37 . Our current model does not include interneurons, which are born in the ventral forebrain and have to migrate dorsally to integrate into cortical circuits 38 .…”
mentioning
confidence: 99%